Cone-beam computed tomography evaluation of canal morphology of maxillary premolars in Malaysian subpopulation using two canals classification - Ahmad Mu’min Mohd Hafiizh; Siti Noraishah Md Yusuf; Siti Hajar Omar; Norazlina Mohammad (Ovid Technologies (Wolters Kluwer Health), 2025)
Indexed